The bright sword : a novel of King Arthur - Grossman, Lev (Viking, 2024)
"Collum, a brilliantly gifted young knight from the provinces, arrives at Camelot two weeks after the Battle of Camlann, hoping to compete for a spot on the Round Table. But he finds the city empty, King Arthur dead, and the Table destroyed. The remaining six knights aren't the mighty heroes, the legends, like Lancelot and Gawain and Tristram and Galahad. These are the survivors, a grab-bag of minor oddball knights from the margins--Sir Palomides, the Saracen Knight; Sir Bedivere, Arthur's one-handed longtime companion; Sir Dagonet, Arthur's fool, knighted as a joke; Sir Dinadan, a cutting wit who's hiding a deep secret. Arthur's death has exposed the splinters of his kingdom, and a void has opened in the heart of Britain. As power-hungry lords from the north descend on Camelot to seize control of the land, Collum is thrust into the front lines. Here lies the battlefield between pagans and Christians, fantasy and empire, power and destiny. Monsters and fairies are reawakening, the moral center is gone, and the fragile alliances that held Britain together are breaking. It is up to the surviving knights, the rebellious sorceress Nimue, and young Collum to avenge Arthur's murder and save Camelot. Can they re-build the Table and bring back the glory that was Camelot? Should they even try? The first major Arthurian epic of the new millennium, full of duels and quests, battles and tournaments, magic swords and Fisher Kings, The Bright Sword is a story about power and hope, and the struggle for the soul of England between the new Christian God and the old gods of fairy. But most of all it's a story about flawed men and women full of strength and pain who are looking for a way to reforge a broken land, in spite of being broken themselves"--